ANALISIS SETTING RENEWABLE FRACTION PADA DESAIN PEMBANGKIT LISTRIK TENAGA HIBRID (BAYU-SURYA) - STUDI KASUS DI DESA NGIJO KABUPATEN MALANG - Mardotillah, Nanda Azizah; Wibawa, Unggul; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
Electrical energy is essential in modern life, with per capita electricity consumption in Indonesia continuing to rise as the economy and urbanization grow. While reflecting positive economic development, this also puts pressure on electricity infrastructure, demanding sustainable electricity generation alternatives. Indonesia has great potential for wind and solar energy, yetutilization is still limited. Ngijo Village in Malang Regency is an example of hybrid power plant implementation, but its success depends on settings such as Renewable Fraction (RF). This study evaluates the potential of renewable energy in Ngijo Village in 2023 using HOMER simulation. Data on solar radiation, wind speed, system component costs, and the number of families usingelectricity were used to determine the RF setting. Results show Ngijo Village has a large solar radiation potential, with the highest average of 6.26 kWh/m²/day, and wind speeds of 1-2 m/s. Higher RF increases production from the Hybrid Power Plant (PLTH) and decreases production from the public grid. RF also affects the economics of the plant, with net present cost and annualized cost increasing as RF increases, while cost of energy decrease. However, at 60% RF, the cost of energy increase again. Keywords: Setting Renewable Fraction, PLTH, Wind, Solar, HOMER, Ngijo Village